A complete traceability methodology between UML diagrams and source code based on enriched use case textual description - Khlif, Wiem; Kchaou, Dhikra; Bouassida, Nadia (Informatica, 2022)
Traceability in software development proves its importance in many domains like change management, customer's requirements satisfaction, model slicing, etc. Existing traceability techniques trace either between requirement and design or between requirement and code. However, none of the existing approaches achieved reliable results when dealing with traceability between requirements, design models and source code. In this paper, we propose an improvement and an extension of our design traceability approach in order to tackle the traceability between design, requirement and code. The fine-tuning of our methodology stems from considering an expanded textual description. A pre-treatment step is added in order to divide the textual description of system functionalities into different parts, each of which represents a specific goal. In fact, the extension consists in extracting an expanded textual description from a natural language text in order to trace between related elements belonging to requirement, design and code while using an information retrieval technique. The proposed method is based on different scenarios (nominal, alternatives and errors), particularly on concepts related to control structures to establish the traceability between artefacts. Furthermore, we implemented our method in a tool allowing the evaluation of its performance. The evaluation is performed on real existing applications that consist in comparing results found by our approach with results found by experts. Our method achieves an average precision of 0.84 and a recall of 0.91 in traceability between requirement, design and code. Besides its promising performance outcomes, our automated method has the merit of generating a traceability report describing the correspondence between different artefacts.